Efektivitas Model Pembelajaran Tipe Talking Stick terhadap Keaktifan Belajar di SMP Negeri 11 Bandar Lampung - Eti Rahmawati; Jamal Fakhri; Fitriani Fitriani (MAN 4 Kota Pekanbaru, 2026)
The following study aims to examine the effect of the Talking Stick cooperative learning model on student learning engagement in Islamic Religious Education (IRE) at SMPN 11 Bandar Lampung. The study used a quantitative approach with a quasi-experimental posttest-only control group design. The research sample consisted of 60 students divided into an experimental class and a control class, each with 30 students. Data were obtained through a Likert scale questionnaire that had been tested for validity and reliability. The analysis results showed that the data had a normal and homogeneous distribution. However, the t-test results obtained a significance value of 0.131 (p > 0.05), which indicated that the application of the Talking Stick model did not significantly affect student learning engagement. This finding indicates that the Talking Stick model does not automatically increase learning engagement in the affective domain in IRE learning. This study emphasizes the importance of using a more adaptive, contextual learning approach that is aligned with student characteristics and value-based learning objectives. Therefore, IRE teachers who wish to continue using this model are advised to integrate it with reflective activities and value reinforcement strategies to ensure that classroom interactions are not only participatory but also affectively meaningful.